Adopting Occupational Health and Safety Management Standards: The Impact on Financial Performance in Pharmaceutical Firms in China - Yang M; Maresova P (Dove Medical Press, 2020)
Minghui Yang,1,2 Petra Maresova1 1Faculty of Informatics and Management, University of Hradec Kralove, Hradec Kralove 50003, Czech Republic; 2International Business School, Guangzhou College of South China University of Technology, Guangzhou, Guangdong 510800, People’s Republic of ChinaCorrespondence: Petra MaresovaFaculty of Informatics and Management, University of Hradec Kralove, Rokitanskeho 62, Hradec Kralove 50003, Czech RepublicTel +420 737 928 745Email petra.maresova@uhk.czBackground and Purpose: In recent years, the frequent occurrence of occupational accidents, illness, and injuries has become a major issue in China. This study aims to investigate the relationship between the adoption of Occupational Health and Safety Management System (OHSMS) standards and financial performance, with a particular focus on the pharmaceutical firms in China.Methods: The study is based on a sample consisting of 125 pharmaceutical firms listed on the Shanghai and the Shenzhen stock exchanges in China for the period 2010– 2018. Each sample firm was evaluated by whether and when it is certified by an OHSMS standard depending on secondary data collected from an independent certification database. Panel-based regression models were employed to explore whether adoption of an OHSMS standard has had an impact on financial performance.Results: The regression results reveal that the adoption of an OHSMS standard positively affects contemporaneous financial performance measured by return on assets (ROA), return on equity (ROE), and earnings per share (EPS). Mixed results were found when financial performance indicators were extended by two years, suggesting that ROE will increase in the second year after a firm is certified with the standard, but EPS will decline in the third year.Conclusion: The study findings empirically show that adoption of an OHSMS standard contributes to better financial performance for pharmaceutical firms of China in the short term. However, executives of pharmaceutical firms need to be aware of the increased costs related to certification renewal and audit in the following periods and exercise their management discretion to achieve a win–win situation between OHSMS implementation and financial benefit.Keywords: occupational health and safety management system, OHSAS 18001, ISO 45001, financial performance, pharmaceutical firm